Perovskite solar cells: An integrated hybrid lifecycle assessment and review in comparison with other photovoltaic technologies. (December 2017) - Ibn-Mohammed, T.; Koh, S.C.L.; Reaney, I.M.; Acquaye, A.; Schileo, G.; Mustapha, K.B.; Greenough, R.
Abstract: Solar cells are considered as one of the prominent sources of renewable energy suitable for large-scale adoption in a carbon-constrained world and can contribute to reduced reliance on energy imports, whilst improving the security of energy supply. A new arrival in the family of solar cells technologies is the organic-inorganic halide perovskite. The major thrust for endorsing these new solar cells pertains to their potential as an economically and environmentally viable option to traditional silicon-based technology. To verify this assertion, this paper presents a critical review of some existing photovoltaic (PV) technologies in comparison with perovskite-structured solar cells (PSCs), including material and performance parameters, production processes and manufacturing complexity, economics, key technological challenges for further developments and current research efforts. At present, there is limited environmental assessment of PSCs and consequently, a methodologically robust and environmentally expansive lifecycle supply chain assessment of two types of PSC modules A and B is also undertaken within the context of other PV technologies, to assess their potential for environmentally friendly innovation in the energy sector. Module A is based on MAPbX3 perovskite structure while module B is based on CsFAPbX3 with improved stability, reproducibility and high performance efficiency. The main outcomes, presented along with sensitivity analysis, show that PSCs offer more environmentally friendly and sustainable option, with the least energy payback period, as compared to other PV technologies. The review and analysis presented provide valuable insight and guidance in identifying pathways and windows of opportunity for future PV designs towards cleaner and sustainable energy production.